Hypoxic, blood flow restriction, or eccentric cycling: Which training intervention is the most effective in elderly individuals? - Tom Citherlet; Gustavo R. Mota; Marco Carletta; Kevin Hayoz; Daniel Pereira Silva; Grégoire P. Millet (Bern Open Publishing, 2024)
Introduction The global rise in the elderly population is accompanied by an increased incidence of non-communicable diseases, including cancers, cardiovascular conditions, or sarcopenia. Therefore, it becomes crucial to find effective strategies to delay the onset or slow down the progression of these diseases. Hypoxic (HYP), blood flow restriction (BFR), and eccentric (ECC) training are promising modalities to mitigate the effects of aging. However, these training strategies have never been compared. Thus, this study aimed to evaluate whether moderate-intensity intermittent training (MIIT) combined with HYP, BFR, or ECC can induce similar or greater effects in strength and muscle mass in the elderly, compared to traditional cycling training (CON). Methods Fifty-five elderly participants completed a four-week MIIT protocol on cycle ergometers, divided into HYP, BFR, ECC, and CON groups. The HYP group trained under hypoxic conditions (inspired oxygen fraction ~14%), BFR group used occlusion cuffs applied proximally on thighs (~350 mmHg occlusion pressure), ECC group trained with an eccentric cycle-ergometer, and the CON group underwent standard cycling training. The first week consisted of 3 sets of 5 min exercise followed by 5 min rest and an additional set was added each week. All groups maintained a 60-rpm cadence, with intensity set at a 14-perceived exertion level on the 6-20 Borg scale. Strength parameters were assessed via isokinetic tests at angular velocities of 30°/s, 90°/s, and 180°/s, as well as isometric and endurance tests. Endurance strength was calculated as a percentage decrement score during 30 repetitions at 180°/s and the rate of force development was calculated on the isometric test. Muscle-bone cross-sectional area (CSA) was measured by integrating thigh circumference measured using a measuring tape, and anterior and posterior adipose tissue thickness assessed with a B-mode ultrasound. Results Post-training, all groups showed increased isometric quadriceps strength (14 ± 15%, p < 0.001) and strength at all angular velocities: 18 ± 17% and 15 ± 21% (30°/s), 17 ± 20% and 20 ± 26% (90°/s), 10 ± 14% and 10 ± 16% (180°/s) for quadriceps and hamstrings respectively, all P < 0.001. No significant group interaction effects were noted, except for hamstring strength at 30°/s (P = 0.038), with no improvements in the ECC group. No changes in the rate of force development or dynamic endurance post-training were noted. Thigh circumference increased (1 ± 2%, p = 0.008), without difference between training modalities. No significant variations in adipose tissue thickness or muscle-bone CSA occurred. The ECC group had higher training intensity (173.2 ± 7.5 W) than HYP (169.6 ± 9.8 W), BFR (169.9 ± 11.6 W), and CON (169.6 ± 8.4 W) groups (p < 0.001). Training heart rate was lower in ECC (104.5 ± 6.6 bpm) compared to BFR (117.5 ± 10.5 bpm; p = 0.007) and CON (122.2 ± 12.3 bpm; p = 0.001), but similar to HYP (112.2 ± 9.4 bpm). Discussion/Conclusion MIIT, regardless of modality, effectively improves muscle strength in the elderly. Unexpectedly, no single training method was superior. Power output reduction has been proposed as an advantage of HYP and BFR modalities but was not observed in the present study. These results advocate for a personalized approach to training prescriptions, considering individual preferences and health conditions. Future research should explore longer training durations and impacts on other health outcomes such as cardiovascular and respiratory health.